Faktor Penyebab Kejenuhan Belajar Al-Qur’an Hadis Pada Peserta Didik Kelas XII Di MA An-Nawawi 03 Kebumen - Mohamad Madum (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2021)
The background of this research is the emergence of the phenoma of student saturation in the learning process in Al-Qur’an Hadis. This researcher focuses on the attitudes of students when, experiencing saturation in learning Al-Qur’an Hadis, this study uses a qualitative method. Based on the data analysis that the resarchers conducted, it was concluded that, when students experienced satiration learning Al-Qur’an Hadis, the would ignore the material conveyed by the teacher by entering the class late in, telling stories with friends, distrubing friends, looking for materials for toys, permission to leave or go to toilet, put your head on the table and sleep during the learning process. As for saturation factor of the students due to physical factors, where students feel physically un well to look of rest and in take of food received is less nutritious. The next factors is that, the spiritual and mentall factors of the student are not well organized according to their puberty period. The last factor is the lack of more attention from Al-Qur’an Hadis teachers to students.